STRATEGI PEMBELAJARAN BAHASA INGGRIS MELALUI COLLABORATIVE WRITING DAN SYNCHRONOUS CORRECTIVE FEEDBACK BAGI GURU SMA/SMK DI SURABAYA - Nukmatus Syahria; Irfan Rifai; Ferra Dian Andanty; Salim Nabhan; Siyaswati Siyaswati (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
Abstract The strategy of collaborative writing as a means of increasing the success of learning English has been widely studied. Most of the research on the two strategies aforementioned emphasized more on the perspective of students and teachers using conventional methods. However, research on how to use collaborative writing strategies and feedback using Google Docs is least investigated. Therefore, this article aims to describe the process of implementing English language learning through collaborative writing training for Senior High School teachers in Surabaya by using Google Docs application. This training was conducted by English Department of the University of Adi Buana Surabaya in collaboration with MGMP (Musyawarah Guru Mata Pelajaran) Bahasa Inggris or English Teacher Working Group as a part of community service. It is held online and was attended by 65 participants for three days. The data were obtained from the survey, language teachers’ reflections, as well as interview and analysed using content analysis. The results of the data analysis show that in addition to increasing teacher knowledge about the two learning strategies – collaborative writing and corrective feedback, the teachers also get hands-on experience applying these learning strategies with the help of technology applications on Google. Moreover, the collaborative writing and corrective feedback learning strategy through Google Docs provides new nuances in learning English and help motivates teachers to write in groups which in turn can increase interest in publication as part of increasing teacher professionalism.Keywords: learning strategy; collaborative writing; synchronous corrective feedback; Google Docs